The Integration and Interaction of Laozi and Christianity - HAN, Huanzhong (Journal of Research for Christianity in China (JRCC), 2025)
Yuan Bujia's Laozi and Christ is an excellent work that promotes the integration of Laozi and Christianity and the sinicization of Christianity. In Yuan Bujia's understanding, Laozi's theory of the Tao and the Christian theory of God are highly isomorphic. The sage mentioned by Laozi is a prophecy of Jesus who would come to the world through "the incarnation of the Word" six or seven hundred years later. Cultivating the Tao according to Laozi's teachings is an embodiment of truly believing in God and his incarnation, Jesus. Yuan Bujia's integration of Laozi and Christianity is very conducive to Chinese Christians' understanding and acceptance of China's inherent excellent traditional culture. It is also very beneficial for Laozi to go global and be understood and accepted by countries that believe in Christianity.
Keywords: Yuan Bujia; Laozi and Christ; integration; sinicization of Christianity